The Effectiveness of Solution-focused Strategies on Coronavirus Anxiety and Mental Toughness in Tehran Female Students during the COVID-19 Pandemic - Pavandi, Marjan; Elmimanesh, Nila (Shahroud Journal of Medical Sciences, 2022)
Background: A serious and urgent concern for the health and well-being of the student population is Coronavirus Disease 2019 (COVID-19). This study aimed to evaluate the effectiveness of a solution-oriented strategic approach on coronary anxiety and mental toughness of female students during the COVID-19 Pandemic.Methods: The research method was semi-experimental with pre-test and post-test design with the control group. The statistical population included all female students of the Payame Noor University of Tehran during the corona outbreak in the academic year 2020-2021. 32 people were selected by purposive sampling method and randomly divided into two groups of experimental (n=16) and control (n=16). Questionnaires such as coronary anxiety and mental toughness were used for data collection. The solution-oriented strategic approach was performed for 8 sessions, 90 minutes each for the experimental group, and the control group received none. To analyze data, multivariate analysis of covariance (MANOVA) and one-way analysis of covariance (ANOVA) was applied as main statistical procedures.Results: The results showed that the Solution-oriented strategic approach was effective in improving mental endurance and coronary anxiety of female students during coronary heart disease and these results continued until the follow-up stage (Pvalue<0.001).Conclusions: This study showed that the solution-based approach could assist references incorrectly identifying the risks, barriers, and crisis points of their lives and in providing them with appropriate insight into the capabilities and resources of the individual's support system.Keywords: Solution-oriented strategic approach, Coronary anxiety, Mental toughness, Female students, COVID-19 Pandemic